The concept of Hiyal in e-commerce : understanding of villagers in Kampung Bintang, Temerloh, Pahang Darul Makmur / Muhammad Shafiq Arzahar - Arzahar, Muhammad Shafiq (Academy of Contemporary Islamic Studies (ACIS), 2018)
This study was to examine the understanding of villagers in Kampung Bintang, Temerloh Pahang related to hiyal in E-Commerce. The objective of this study is to determine the level of awareness of Kampung Bintang residents in online transaction tricks. Moreover, it is to conduct a study on of Kampung Bintang residents to assess their understanding of the concept of Hiyal (Trick) in E-Commerce and analyze the studies that have been conducted on the villagers of Kampung Bintang about Hiyal in E-Commerce. Kampung Bintang, Temerloh Pahang serves as the location for the study to assess their understanding of the hiyal in E-Commerce. To carry out this study, the authors used questionnaire and observation method to determine the level of understanding of the villagers. Data was analyzed and described in the study and explanation. In conclusion, the understanding among villagers needs to be improved. And make solutions, it is expected that the villagers aware about the tricks in E-Commerce.